2014
DOI: 10.1037/a0038016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of subjective aging on health and longevity: A meta-analysis of longitudinal data.

Abstract: Evidence is accumulating on the effects of subjective aging-that is, how individuals perceive their own aging process-on health and survival in later life. The goal of this article is to synthesize findings of existing longitudinal studies through a meta-analysis. A systematic search in PsycInfo, Web of Science, Scopus, and Pubmed resulted in 19 longitudinal studies reporting effects of subjective aging on health, health behaviors, and longevity. The authors combine the outcomes reported in these studies using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
322
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 354 publications
(368 citation statements)
references
References 72 publications
19
322
2
5
Order By: Relevance
“…A more recent report revealed an association between negative age stereotypes held earlier in life and a later increased risk for Alzheimer's brain pathology (Levy et al 2016). Moreover, a meta-analysis of 19 longitudinal studies concluded that positive subjective ageing (defined as positive ageing attitudes and youthful identities) contributes to better health and increased longevity in later life (Westerhof et al 2014). Potential explanations may include that self-ageist ideas or negative views on ageing make it less likely for older adults to embrace positive health behaviors such as physical activity (Wurm et al 2010), take preventive health measures, or adhere to recommended treatments (Levy and Myers 2004).…”
Section: Self-ageism In the Health Care Settingmentioning
confidence: 99%
“…A more recent report revealed an association between negative age stereotypes held earlier in life and a later increased risk for Alzheimer's brain pathology (Levy et al 2016). Moreover, a meta-analysis of 19 longitudinal studies concluded that positive subjective ageing (defined as positive ageing attitudes and youthful identities) contributes to better health and increased longevity in later life (Westerhof et al 2014). Potential explanations may include that self-ageist ideas or negative views on ageing make it less likely for older adults to embrace positive health behaviors such as physical activity (Wurm et al 2010), take preventive health measures, or adhere to recommended treatments (Levy and Myers 2004).…”
Section: Self-ageism In the Health Care Settingmentioning
confidence: 99%
“…Going further, increases in optimism over a 4-year period were associated with better self-rated health and fewer chronic illnesses [33] . Wurm and Benyamini [34] showed that dispositional optimism may also buffer the hazardous effects of negative attitudes toward aging that have otherwise been shown as a risk factor for physical health [35] .…”
Section: Perception Of Time As Time-related Evaluations Attitudes Amentioning
confidence: 99%
“…Altersbilder und Altersdiskriminierungserfahrungen sind bedeutsam für die Gesundheit und das Wohlergehen von Menschen (Westerhof et al 2014;Sutin, Stephan, Carretta, & Terracciano 2015). …”
Section: Diskussion Und Implika Onenunclassified